ANALISIS HIRA (HAZARD IDENTIFICATION AND RISK ASSESSMENT) PADA INDUSTRI TAHU SERASI BANDUNGAN BARU SEMARANG - Alauddin, Muhammad Rifqi; Denny, Hanifa Maher; Jayanti, Siswi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
HIRA is one of many risk valuation methods that can be used to value which hazard is able to provoke the biggest risk. It’s done by considering the probability and the impact. Tahu Serasi Bandungan Baru Industri is one of many informal sector industries having hazard potential to the work environment and work process. This research’s purpose is to identify hazard potential, risk assessment , describe current hazard control and recommend hazard control means to decrease work accident risk. This research is done in two location of Tahu Serasi Bandungan Baru production by using explanatory research with 14 respondents which consist of 12 main informant and 2 triangulation informant. In detail, each location has 6 main informant and 1 triangulation informant. Work process in this tofu industri is divided into two, odd section and milling section. Based on research some hazard potentials are learned. Those are cramp, slip, process tools wedge, process tools struck down, mold, hot soybean extract, combustion fumes, electric shock, noise and fire. Tahu Serasi Bandungan Baru Industri has done some hazard control means by giving break time and personal protective equipment to employees.